Bioelectronic Hydrogels: Exemplifying the Synergy Between Biopolymers and Conjugated Polymers - Thanh Nhi Tra; Kristina Fidanovski; Damia Mawad (Macromolecular Materials and Engineering)
Abstract Conductive hydrogels are a potential platform for 3D cell culture, especially in bioelectronic interfaces, enabling the integration of electronic and mechanical signals as biological cues. Biopolymer‐based conductive hydrogels offer significant advantages thanks to their inherent flexibility and their renewable and biocompatible properties, in combination with the conductivity of the hydrogel network. However, hydrogels' vulnerability to mechanical failure limits their durability in bioelectronic applications. To address this, self‐healing conductive hydrogels with reversible dynamic networks have emerged. These materials are capable of repairing themselves after damage and closely mimic the healing characteristics of living tissues. This self‐healing capability thus promotes the reliable and long‐lasting use of bioelectronic devices. This review first examines the individual characteristics of conductive hydrogels, namely electrical conductivity from the conjugated polymer and mechanical cues from the biopolymer, in terms of their influence on cellular activities. Subsequently, recent advancements in biopolymer‐based conductive hydrogels are discussed, with a focus on their fabrication method and ability to modulate specific cell functions. Finally, the advancements in self‐healing hydrogel bioelectronics are summarized, focusing on the variety of self‐healing mechanisms and the corollaries for enhanced bioelectronic longevity.